CHARACTER EDUCATION MODEL IN EARLY AGE CHILDREN - Suryana, Sawa (Indonesian Journal of Early Childhood Education Studies, 2013)
Character education in addition to developing and strengthening personal potential and also filter out external influences which could ultimately shape the character of the students for the better. Efforts to establish this character solely conducted in educational institutions through a series of learning activities through a series of subjects and self-development activities conducted at the inside and outside of school. Habituation-refraction in everyday life also made, such as: religious attitude, honesty, discipline, tolerance, hard work, love peace, responsibility, of etc.These values would need to be fostered, which in turn can shape the character of individual learners which in turn is faces life of a nation. Hams in character education should always emphasize the importance of three components, namely good moral character or knowledge ofmoral knowing, moral feeling or sense of moral action and moral or immoral acts. This is necessary so that learners can understand, feel and do not run as well as virtues.Â